Pola kepadatan populasi vektor penyakit DBD di permukiman penduduk bantaran Sungai Martapura Kecamatan Martapura Timur Tahun 2017 - Yohanes Joko Supriyadi; Darmiah Darmiah; Yuniarti Suryatinah (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2018)
Martapura river water is one of the source of water used for daily use by residents who live along the banks of the river Martapura. Almost every house along the river Martapura does not have adequate clean water facilities and is highly dependent on river water. The objective of the study was to know the pattern of population density of dengue fever vector in residential area of ​​river Martapura. This type of analytic research, using a cross sectional design. The population of all Aedes sp mosquitoes and all residents in the residential area of ​​river Martapura. The sample is partially Aedes sp mosquitoes and residents in the residential area of ​​the river Martapura river, the village Antasan Senor, Antasan Senor Ilir, and the village of Mekar). Purposive Sampling Sampling Technique. Methods of gathering observations, interviews and identification. Analytical data processing and analysis with one way ANOVA test. The results showed that the population density vector category "High" DF = 4.7 and ABJ 71.7%. The result of statistical test of population vector density pattern there is no significant difference (p-value> 0,05). The environmental condition of the settlement is quite clean, breading place of the existence of larvae is not found, the number of TPA varies in the form of plastic, rubber, cement, iron / aluminum. Type / material of positive landfill larvae made of plastic material. Suggestion of research, for related institution to socialize and mobilize community in PSN activity of 3M + movement routinely, larva survey once a week, train Jumantik officer, public health education activity and integrated vector eradication (physical, chemical or biological) and community PHBS found the family / community experiencing symptoms of dengue disease immediately report / bring to the nearest health officer / facility.